Green tourism innovation model for ecologically based tourism villages in Tabanan Bali - Dewa Ayu Suryawati; I Gede Wiramatika (Bahasa Indonesia, 2026)
The rapid expansion of tourism in Bali presents both opportunities and challenges for the preservation of its natural and cultural assets. This study proposes a Green Tourism Innovation Model as an integrated framework for establishing an Ecology‑Based Tourism Village in Nyambu Village, Tabanan. Grounded in the village’s intrinsic natural endowments, cultural heritage, and traditional agricultural systems, the model weaves together the principles of environmental sustainability, community empowerment, and digital technology. A qualitative research design was adopted, encompassing in‑depth interviews with key stakeholders including local government officials, village head, local communities and academic experts to capture a comprehensive understanding of the village’s socio‑ecological dynamics and governance context. Thematic analysis of interview data informed the articulation of seven inter‑linked pillars that constitute the green tourism innovation model. The results of this study produce a tourism village development model that focuses on the pillars of Policy & Incentives, Community Empowerment, Technology Integration, Sustainable Livelihoods, Smart Tourism Management, Environmental Stewardship, and Visitor Experience. The resulting green tourism innovation model framework provides a replicable blueprint for transforming traditional villages into resilient, low‑carbon tourism destinations. This research contributes to the green tourism literature and provides practical guidance for policymakers, developers, and community leaders who want to transform traditional villages into sustainable tourism destinations.